Tourists' perception on the environmental quality of Port Dickson as sustainable tourism destination - Mohd Nasir, Nadia; Ibrahim, Mansor; Mohamed Osman, Mariana (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
This paper discusses the tourists' perception on the impact of tourism development towards the environmental quality of Port Dickson. It aims to examine the visitors’ responses towards the current environmental quality of the study area. Port Dickson is now having crucial environmental problems in spite of being one of the famous tourist spots in Malaysia. There are several aspects of the environment needing to be focused on which are water, air, environment and noise pollution. Questionnaire survey was distributed to a total of 120 visitors coming from all over Malaysia. The result helped the author to identify the tourists' perceptions on the environmental issues and problems in Port Dickson. Further analysis and discussion shows that this situation can be improved by a few means of sustainable tourism planning strategies, appropriate IT applications with active and effective public participation.